FAKTOR PENENTU BERTEMPAT TINGGAL PADA KAWASAN KUMUH DI KOTA MALANG BERDASARKAN TEORI DOXIADIS - Endratno Budi Santoso; Ledy Vithalia Therik (Diponegoro University, 2016)
The sustainability process of a human settlement depend on how the perception of its people. Jodipan condition, as a slum area in Malang City, influenced by several factors, one factor named ekistic factor as in Doxiadis theory. This research’s aim is to analyze key factor for the resident to stay, and tries to identify how this ekistic factor related and influenced with people perception in choosing settlement location. This research run by primary and secondary survey, and also helps by observation and questionnaire distribution at two priority location. By using likert scale approach and multiple regression analysis, this research also using some of statistical test, such as T Test, F Test, and multicolonierity test. After analysis process, this research found that shell variable (such as building of the house) as the main reason for the resident to stay at Jodipan slum.